Impact of subjective well-being on physical frailty in middle-aged and elderly Japanese with high social isolation. - Kai Tanabe; Yuki Sugawara; Eiichi Sakurai; Yoichi Motomura; Yukihiko Okada; Akiko Tsukao; Shinya Kuno (PLoS ONE, 2024)
Social isolation exacerbates physical frailty and is associated with subjective well-being. Even those with high levels of social isolation may have different health statuses depending on the type of isolation and their subjective well-being. However, the effect of subjective well-being on the relationship between social isolation and physical frailty remains unclear. This study examined whether the risk of physical frailty was the same for individuals with social isolation according to high and low subjective well-being. The study participants included 1,953 middle-aged Japanese adults aged 45 years and older. Physical frailty was assessed using a modified version of the Fried phenotype criteria. Probabilistic Latent Semantic Analysis was used to classify participants according to social isolation indicators. Subsequently, we focused on the groups with high social isolation and classified them according to whether their subjective well-being was high or low. Subjective well-being was evaluated using the Shiawase and Ikigai scales, which are concepts used in Japan. Finally, we used survival time analysis to examine the relationship between Shiawase or Ikigai and physical frailty in groups with high social isolation. The participants were classified into four groups based on their social isolation status. The physical frailty rate of the high social isolation class was 37.0%, which was significantly higher than that of the other classes. Survival time analysis revealed that among people with high social isolation, those with high Shiawase and Ikigai had a significantly lower risk of physical frailty than those with low Shiawase and Ikigai. All individuals with high social isolation are not at a high risk of physical frailty. The findings reveal that even those with high level of social isolation may have a lower risk of physical frailty if their subjective well-being is high. These results will contribute to promoting the prevention of frailty in middle-aged and older adults.